2022
DOI: 10.1002/cam4.5367
|View full text |Cite
|
Sign up to set email alerts
|

High endothelial venules in intracranial germinomas: Implications for lymphocytes infiltration

Abstract: BackgroundReactive lymphocytes are substantial components of germinoma, which are believed to be related to the favorable prognosis of this intracranial tumor and better response to immunotherapy. However, the mechanisms managing the recruitment of lymphocytes are poorly understood. High endothelial venules (HEVs) are specialized blood vessels that play key roles in lymphocyte tra cking in Lymph nodes. These vessels are associated with lymphocytes in ltration in chronic in ammatory diseases and various maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The presence of HEVs was associated with abundant infiltration of CD3+T, CD20+B, and CD8+T cells. Higher HEV levels were associated with a favorable prognosis for germinomas [ 1 ]. Takami et al found that NGGCTs had significantly higher levels of immune cell infiltration compared to germinomas in their transcriptomic study [ 31 ].…”
Section: Immune Landscapementioning
confidence: 99%
“…The presence of HEVs was associated with abundant infiltration of CD3+T, CD20+B, and CD8+T cells. Higher HEV levels were associated with a favorable prognosis for germinomas [ 1 ]. Takami et al found that NGGCTs had significantly higher levels of immune cell infiltration compared to germinomas in their transcriptomic study [ 31 ].…”
Section: Immune Landscapementioning
confidence: 99%